2011
DOI: 10.1111/j.2041-210x.2010.00047.x
|View full text |Cite
|
Sign up to set email alerts
|

Stable isotope analysis: modelling lipid normalization for muscle and eggs from arctic mammals and birds

Abstract: 2Chaire de recherche du Canada en conservation des e´cosyste`mes Nordiques et Centre d'e´tudes nordiques, Universite´du Que´bec aR imouski, Rimouski, QC G5L 3A1, Canada Summary 1. Lipids are more depleted in 13 C than proteins. Variable lipid contents in tissues affect therefore the measurements of stable carbon isotope ratios. Model based (also called mathematical) normalization has been suggested to correct d 13C values using the ratio of carbon to nitrogen (C ⁄ N) as a proxy for lipid content. This approach… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
71
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 57 publications
(75 citation statements)
references
References 33 publications
4
71
0
Order By: Relevance
“…This suggests that lipid reserves in muscle of emaciated individuals were greatly reduced or exhausted. Overall, our results suggest that C/N of muscle may serve as a general indicator of nutritional condition in owls, with higher C/N indicative of greater lipid reserves (Okumura et al 2002;Post et al 2007;Ehrich et al 2010). This assay is more convenient and less invasive than other methods for quantifying nutritional condition, such as the measurement of bone marrow (Thouzeau et al 1997) or whole body homogenization followed by lipid extraction (Baduini et al 2001).…”
Section: Fasting and Measures Of Nutritional Conditionmentioning
confidence: 95%
“…This suggests that lipid reserves in muscle of emaciated individuals were greatly reduced or exhausted. Overall, our results suggest that C/N of muscle may serve as a general indicator of nutritional condition in owls, with higher C/N indicative of greater lipid reserves (Okumura et al 2002;Post et al 2007;Ehrich et al 2010). This assay is more convenient and less invasive than other methods for quantifying nutritional condition, such as the measurement of bone marrow (Thouzeau et al 1997) or whole body homogenization followed by lipid extraction (Baduini et al 2001).…”
Section: Fasting and Measures Of Nutritional Conditionmentioning
confidence: 95%
“…In addition, samples of main prey were analyzed: muscle of Siberian and collared lemmings; egg content of passerines, waders, and geese; muscle samples of birds accidentally killed in snap traps or of dead chicks; and samples of fish (see Appendix 1 for species list and sample numbers). Preparation of muscle and egg samples was carried out as described by Ehrich et al (2010). Fur samples were washed in 2:1 chloroform-methanol to remove hair surface fat, dried, clipped to very small pieces with scissors, and weighed as for the muscle samples.…”
Section: Stable Isotope Analysis: Diet Inferencementioning
confidence: 99%
“…Isotope ratios were determined by combustion in a mass spectrometer at the Stable Isotopes in Nature Laboratory (SINLAB, Canadian Rivers Institute, Biology Department, University of New Brunswick, Fredericton, New Brunswick). Because the presence of lipids in samples can introduce a bias in δ 13 C, lipids were extracted chemically from some egg samples, and the rest of the samples were corrected for lipid content arithmetically, using the equations from Ehrich et al (2010).…”
Section: Stable Isotope Analysis: Diet Inferencementioning
confidence: 99%
“…The lipid content of a tissue is influenced by several factors besides just the food source (e.g. species, tissue type, reproductive stage, gender, nutritional state), and a high or highly variable lipid content can therefore mask the dietary δ 13 C signal, thereby making inter-or intra species comparisons and diet reconstructions difficult (Ehrich et al, 2011;Hoffman and Sutton, 2010;Post et al, 2007). Indeed, it has been reported that the lipid content in gills may vary substantially between species and with growth conditions (Serrano et al, 2007;Vollaire et al, 2007).…”
Section: Introductionmentioning
confidence: 99%